The Business of Creating Games: How to Make Positive and Effective in Multiple Area of a Business by Creating Games - Arsa Widitiarsa Utoyo (Bina Nusantara University, 2016)
The use of digital games and gamification has showed potential to improve many aspects of how businesses provide education and communicate with consumers. Nevertheless, there is still a requirement for better considerate of how the adoption of games and gamification would influence the process of decisionmaking for customer and organizations across different industry. This article provides a structured review of existing literature on the use of games in the business ecosystem, and seeks to consolidate findings to address research questions regarding their perception, proven efficiency, and identifies key areas for future business. The findings highlight that serious games can have positive and effective impacts in multiple areas of business, including education, decision-support, marketing and consumer outreach. They also emphasize the challenges and pitfalls of affecting serious games and gamification principles within a business context, and discuss the implications of development and evaluation methodologies on the success of a game-based solution.